Fastidious anaerobe agar compared with Wilkins-Chalgren agar, brain heart infusion agar, and brucella agar for susceptibility testing of Fusobacterium species. - Brazier, J S (1990)
Fastidious anaerobe agar supported the growth of 82 strains of fusobacteria better than brain heart infusion agar, brucella agar, and Wilkins-Chalgren agar. Fastidious anaerobe agar showed less hazing and fewer tailing endpoints with beta-lactam antibiotics. Whole-blood supplementation improved the performance of all media. Wilkins-Chalgren agar without blood failed to support the growth of 17% of the strains. All Fusobacterium ulcerans strains were resistant to clindamycin.